2011
DOI: 10.1007/s00468-011-0580-8
|View full text |Cite
|
Sign up to set email alerts
|

Calcium addition at the Hubbard Brook Experimental Forest increases the capacity for stress tolerance and carbon capture in red spruce (Picea rubens) trees during the cold season

Abstract: Red spruce (Picea rubens Sarg.) trees are uniquely vulnerable to foliar freezing injury during the cold season (fall and winter), but are also capable of photosynthetic activity if temperatures moderate. To evaluate the influence of calcium (Ca) addition on the physiology of red spruce during the cold season, we measured concentrations of foliar polyamines and free amino acids (putative stressprotection compounds), chlorophyll (a key photosystem component), and sapwood area (a proxy for foliar biomass), for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 60 publications
(85 reference statements)
1
28
0
Order By: Relevance
“…Transpiration could increase either because of an increased number of stomata (i.e., more foliage on existing trees and new regeneration) or increased water-loss rate from stomata. Our evidence of increased LAI, and past measurements of greater crown density (11), foliar biomass (29), and seedling regeneration (30) at HBEF following Ca addition suggests that this ET response was because of an increased number of stomata. (Fig.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…Transpiration could increase either because of an increased number of stomata (i.e., more foliage on existing trees and new regeneration) or increased water-loss rate from stomata. Our evidence of increased LAI, and past measurements of greater crown density (11), foliar biomass (29), and seedling regeneration (30) at HBEF following Ca addition suggests that this ET response was because of an increased number of stomata. (Fig.…”
Section: Resultsmentioning
confidence: 50%
“…Responses to wollastonite application have included significantly improved photosynthetic function (33), larger sapwood area (an indicator of greater foliar biomass) (29), increased sugar storage and oxidative protection (34), higher phosphorus content of foliage (35), greater mycorrhizal abundance (30), and a more vigorous sugar maple population (30,36) in W1 compared with other untreated HBEF watersheds. Other plot-scale wollastonite additions at the HBEF, but outside of W1, caused increased crown vigor and xylem basal area (11), stimulated fine-root length by ∌300% (37), and resulted in generally more decline-resistant trees (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were also conducted to demonstrate that PAs played a role in providing cold tolerance to red spruce (Schaberg et al, 2011). These studies further showed that Put content reverted back to normal homeostatic levels upon amelioration of the stress factor(s).…”
Section: Polyamines As Metabolic Markers Of Long-term Environmental Smentioning
confidence: 99%
“…GDM can accommodate this by including geographic (temporal) distance as a covariable, but in our dataset, this created collinearity with environmental predictors. While the shift in community composition could result from natural succession, manipulative experiments have shown the direct effects of atmospheric pollution on forest tree physiology and health (Schaberg et al, ), which provides additional evidence that sulphate deposition is a major driver of forest community change.…”
Section: Discussionmentioning
confidence: 99%